Social Representation of Body in Individuals with Body Dysmorphic Disorder-Like Symptoms: The Effects of Social Media and Social Groups - Razaghi Kashani, Shamim (Université d'Ottawa / University of Ottawa, 2025)
Background: Body concerns are prevalent among Canadian youth, considering social media, peers, and family playing a significant role in shaping these representations. This study investigates the social representations of body among youth with and without Body Dysmorphic Disorder (BDD)-like symptoms. By using Social Representation Theory, the study investigates how sociocultural factors contribute to body concerns and explores the differences in how these factors influence individuals with various levels of BDD-like symptoms. Method: A mixed-method approach was utilized, including two phases. Phase 1 employed a mixed-methods approach, combining quantitative and qualitative analyses to asses the prevalence of BDD-like symptoms across socio-demographic factors and to investigate the social representations of the body. To assess associations between BDD symptoms and demographic variables, a chi-square tests and logistic regression were used, while verbal association tasks, frequency-rank analysis was performed to examine the central and peripheral elements of body representations. In phase 2, semi-structured interviews have been conducted to compare the social representation of body between participants with and without BDD-like symptoms. In the qualitative section, thematic analyses were performed to investigate the meanings behind the units that form the social representations of the body, with word clouds visualizing how these representations were anchored. In the quantitative analysis, chi-square tests examined the associations between BDD-like symptoms and theme sub-categories. SRT concepts such as anchoring and objectification were used to analyze the data. Results: Results from article 1 showed significant differences in SR structures between the two groups. Participants with BDD-like symptoms exhibited a more appearance-focused and negative view of body, while those without BDD-like symptoms demonstrated a broader, more positive perspective. In article 2, qualitative findings revealed that individuals with BDD-like symptoms were more influenced by external factors, such as social media, family, and peers, while those without BDD-like symptoms attributed their representation of body to internal factors, including cultural values and personal thought processes. These results indicate that individuals with BDD-like symptoms are more susceptible to societal pressures regarding appearance, which play a critical role in shaping their representation of body. Social media, peers, and family were found to be key contributors to these representations, with social media having the strongest impact on participants with BDD-like symptoms. In article 3, the outcomes extend these insights by exploring the implications of SRT for social work practice. Social work interventions that emphasized media literacy, body positivity, and community support were identified as critical for transforming negative representations into adaptive, health-oriented frameworks. These findings highlight the transformative potential of integrating SRT into social work interventions to address body dissatisfaction and BDD-like symptoms among youth. Conclusion: The study shed light on meaningful differences in how people with and without BDD-like symptoms perceive their bodies, emphasizing the role of societal influences in shaping social representation of body. To help individuals with BDD-like symptoms, interventions should emphasis on re-anchoring individual’s body representations in health and functionality, rather than appearance. Promoting media literacy and fostering a positive body representation through family and peer support can mitigate the negative effects of societal beauty ideals. By integrating SRT into practice, social workers can help individuals with BDD-like symptoms re-anchor their body representations in positive, health-oriented frameworks rather than appearance-focused ideals.
Keywords: body dysmorphic disorder; social representation theory; body image; social media; peer; family; youth; Canadian youth; social work practice; intervention